A medical approach to the treatment of atraumatic spontaneous spleen ruptures - Dogan, Serhat; Gundes, Ebubekir; Donder, Yunus; Gulcan, Huseyin; Baburoglu, Mehmet (Annals of Medical Research, 2021)
None